2021
DOI: 10.1016/j.tibs.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Galvanization of Protein–Protein Interactions in a Dynamic Zinc Interactome

Abstract: The presence of Zn 2+ at protein-protein interfaces modulates complex function, stability, and introduces structural flexibility/complexity, chemical selectivity, and reversibility driven in a Zn 2+ -dependent manner. Recent studies have demonstrated that dynamically changing Zn 2+ affects numerous cellular processes, including protein-protein communication and protein complex assembly. How Zn 2+ -involved protein-protein interactions (ZPPIs) are formed and dissociate and how their stability and reactivity are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 112 publications
0
61
0
Order By: Relevance
“…A Cys/His claw coordinates zinc at the protein interface Most proteins bind zinc through Cys or His residues (Kocy1a et al, 2021). In line with this notion, the zinc ions at the interface between FEM1B and FNIP1 are coordinated by one Cys (C186) and two His residues (H185 and H218) of FEM1B and three Cys residues (C580, C582, and C585) and one histidine (H587) of FNIP1 (Figures 2A and 2B).…”
Section: Zinc-dependent Recognition Of Reduced Fnip1mentioning
confidence: 56%
“…A Cys/His claw coordinates zinc at the protein interface Most proteins bind zinc through Cys or His residues (Kocy1a et al, 2021). In line with this notion, the zinc ions at the interface between FEM1B and FNIP1 are coordinated by one Cys (C186) and two His residues (H185 and H218) of FEM1B and three Cys residues (C580, C582, and C585) and one histidine (H587) of FNIP1 (Figures 2A and 2B).…”
Section: Zinc-dependent Recognition Of Reduced Fnip1mentioning
confidence: 56%
“…Nucb1, the paralogue of Nucb2, was previously characterized [48] as a Zn 2+ sensor with a high affinity for Zn 2+ with two Zn 2+ -binding sites ( K d = 32 nM). In contrast, the fitted complex formation constants for both Zn 2+ -binding sites of hsNucb2 are in the range of 10 -5 M and seem to be significantly lower than those of Nucb1 [48] , and hsNucb2 is characterized as a weak Zn 2+ -binding protein, as Zn 2+ is tightly buffered in the cell at concentrations in the low nanomolar to picomolar range [99] . Nucb2 amino acid sequences were determined to possess only one putative Zn 2+ binding site, which might implicate these protein differences [48] .…”
Section: Discussionmentioning
confidence: 77%
“…It was shown that the sea cucumber complex accumulates various elements, including those contained in very low concentrations in seawater. Some studies have shown that various metal ions can significantly affect the stability of complexes of very different nature, consisting of charged, hydrophobic and hydrophilic molecules [ 15 , 16 ], as well as proteins and nucleic acids [ 17 , 18 , 19 , 20 , 21 ]. The data indicate that metal-dependent interactions are formed, in addition to hydrogen bonds between the complex components [ 14 ].…”
Section: Introductionmentioning
confidence: 99%